Understanding the semantics of phrasal verbs - Huwari, Ibrahim Fathi; Erkir, Sarp; Alwreikat, Emad Abedalaziz; Alqaryouti, Marwan Harb; Alshewiter, Kosay Moneer (International Journal of Innovative Research and Scientific Studies, 2025)
The present paper aims to investigate and examine the semantic features of phrasal verbs at the EFL level. The main objectives of conducting this study are to recognize some semantic features associated with language acquisition and to review the semantic structures of these phrasal verbs. Because of their intricate semantic patterns, which include polysemy and idiomatic usage, phrasal verbs (PVs) pose a substantial barrier to students learning English as a foreign language (EFL) as well as second language (L2) learners. The importance of phrasal verbs in the English language, as well as the difficulties learners encounter in mastering them, are examined in the present paper. PVs are quite common in both spoken and written English, according to the statistical investigation of corpus data, such as the British National Corpus (BNC), underscoring their crucial role in developing fluency. Despite being widely used, PVs can be difficult because of their polysemous character and erratic verb-particle combinations. The understanding of polysemy in L2 learners has not received enough attention in the literature, which has concentrated on receptive and productive knowledge regarding PVs. This study looks at the semantic characteristics of PVs, classifying them as literal, semi-transparent, and idiomatic. It also highlights the necessity of specialized teaching strategies to assist students in navigating these complications. The study concludes that in order to enhance both comprehension and production in EFL situations, language teaching must pay close attention to PVs' complex syntactic and semantic characteristics. Achieving native-like fluency and competency in English, especially in casual speech, requires effective mastery of PVs. Finally, this paper proposes that as lexical items, phrasal verbs are certainly one of the greatest problematic tasks in education. This paper additionally offers the related past studies on this subject and presents the outcomes of these studies.